Predictors of recurrent strictures after oesophageal atresia repair - Aworanti, Olugbenga; Landi, Ezio Giulio; Mortell, Alan (Journal of Neonatal Surgery, 2021)
Background: Anastomotic strictures continue to complicate the outcome after oesophageal atresia (OA) repair. Multiple variables contribute to the development of strictures, and oesophageal dilatations are the mainstay of treatment. We aim to analyse the factors that impact the timing for initiation of oesophageal dilatations, the duration, frequency, and success of the dilatation regimen for OA. Methods: It was a retrospective review of data (13-year) of children who underwent repair for Gross type C OA (OA with distal tracheo-oesophageal fistula). Delayed anastomosis was performed for long gap OA. Leaks were clinically obvious or identified on contrast swallow. Strictures that were symptomatic underwent oesophageal dilatations. Results: The data of 72 children were analysed. The stricture rate was 37.5%. Ten had delayed repair, out of which 50% developed strictures compared to 35.5% who had a primary repair (P=0.48). There was no statistical difference in the mean birth weight (BW) and gestational age (GA) of children who developed strictures compared to those with no strictures (2.74kg vs 2.63Kg; P =0.548; 37.4 weeks vs 37.3 weeks; P=0.9). Children that underwent a delayed repair required significantly more dilatation sessions (12 vs 2 median sessions; P =0.001) and had a significantly prolonged duration of treatment (610 vs 63 median days; P = 0.013). There was a significant negative correlation between the GA and BW and the number of dilatation sessions required (P=0.03 and P=0.02, respectively). Linear regression revealed that delayed repair was the most important factor related to the number of dilatation sessions required (p <0.001); this was followed by lower GA or BW (p = 0.0265) and early onset of dilatations (p=0.0471). Conclusions: The early onset of oesophageal dilatation for oesophageal strictures or when they occur in premature babies or those that have had a delayed repair, it should be anticipated that they would be refractory or recurrent.